EMPIRICAL STUDY OF THE CHARACTERISTICS OF THE EXPERIENCE OF LONELINESS BY TEENAGERS (Psychology Travelogs, 2023)
The article presents the results of an empirical study of teenagers' experience of loneliness. A description of the techniques and methods used in the research is presented (the methodology «Diagnosis of the level of subjective feeling of loneliness» (by D. Rasse, M. Ferguson); the diagnostic questionnaire «Loneliness» (by S. Korchaginf), authorial questionnaire «I and Loneliness» (by L. Podkorytova and I. Makaruk) and an associative experiment in the form of a questionnaire).According to the methods «Diagnosis of the level of subjective feeling of loneliness» (by D. Rasse, M. Ferguson) and the diagnostic questionnaire «Loneliness» (by S. Korchagina) it was found that the level of experiencing loneliness of our researched teenagers is average, but there is a significant number of teenagers who are characterized by a deep feeling of loneliness.According to the results of the questionnaire and the associative experiment, it was found that loneliness is experienced by the studied teenagers mainly as a normal, but unpleasant phenomenon, associated with the emotions of sadness, fear, anxiety, a feeling of emptiness and uselessness. Teenagers for whom loneliness is a pleasant, comfortable and creative state have also been identified.It was also found that most of the studied teenagers, when they feel lonely, engage in various types of creative activities, mainly visual ones (painting, needlework, origami).According to the obtained results, a there was made a training program for psychological work with teenagers who experience loneliness. The training uses elements of art therapy, psychogymnastics, games, self-study exercises, brainstorming, group discussion, etc. There are has 10 lessons, each lasting 40-60 minutes, in the program.Prospects for further research are seen in the expansion of the sample and psychodiagnostic tools for a more thorough study of the experience of loneliness among adolescents, in particular, the identification of gender characteristics of the experience of loneliness, the characteristics of the experience of loneliness in other age groups, and the verification of the effectiveness of the program of work with adolescents experiencing loneliness developed by us.
Keywords: loneliness; teenagers; perception; experiences